Pediatric Stroke: Clinical Findings and Radiological Approach. (23rd March 2011) - Lanni, Giuseppe; Catalucci, Alessia; Conti, Laura; Di Sibio, Alessandra; Paonessa, Amalia; Gallucci, Massimo
Abstract : This paper focuses on radiological approach in pediatric stroke including both ischemic stroke (Arterial Ischemic Stroke and Cerebral Sinovenous Thrombosis) and hemorrhagic stroke. Etiopathology and main clinical findings are examined as well. Magnetic Resonance Imaging could be considered as the first-choice diagnostic exam, offering a complete diagnostic set of information both in the discrimination between ischemic/hemorrhagic stroke and in the identification of underlying causes. In addition, Magnetic Resonance vascular techniques supply further information about cerebral arterial and venous circulation. Computed Tomography, for its limits and radiation exposure, should be used only when Magnetic Resonance is not available and on unstable patients.